Controllable defect engineering to enhance the corrosion resistance of Cr/GLC multilayered coating for deep-sea applications. (1st May 2022) - Liu, Yingrui; Li, Shuyu; Li, Hao; Ma, Guanshui; Sun, Lili; Guo, Peng; Ke, Peiling; Lee, Kwang-Ryeol; Wang, Aiying
Abstract: A cleaning intervention is introduced to control the growth defect of Cr/GLC multi-layered coating to avoid premature failure in the deep-sea environment. The results demonstrated that the introduction of the cleaning intervention significantly decreased the penetrating defect density as expected, together without deteriorating the superior mechanical and tribocorrosion properties. The localised corrosion resistance was improved dramatically in the simulated deep-sea environment. It was illustrated that controllable defect engineering can be an effective strategy for improving the anti-tribocorrosion performance of GLC coatings for harsh deep-sea applications. Graphical Abstract: ga1 Highlights: Controllable defect engineering was introduced to control the growth defect. Coating structure does not change over the application of cleaning process. Penetrating defect density decreases after conducting cleaning intervention. Localized corrosion resistance improves in simulated deep-sea environment.